2021
DOI: 10.1002/hbm.25551
|View full text |Cite
|
Sign up to set email alerts
|

Motor and higher‐order functions topography of the human dentate nuclei identified with tractography and clustering methods

Abstract: Deep gray matter nuclei are the synaptic relays, responsible to route signals between specific brain areas. Dentate nuclei (DNs) represent the main output channel of the cerebellum and yet are often unexplored especially in humans. We developed a multimodal MRI approach to identify DNs topography on the basis of their connectivity as well as their microstructural features. Based on results, we defined DN parcellations deputed to motor and to higher‐order functions in humans in vivo. Whole‐brain probabilistic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Second, the dentate nuclei are strongly affected in SCA3. Cerebellar nuclei are the main output structures of the cerebellum, and similar to the cerebellar cortex there is compartmentalization of the dentate nuclei in motor and cognitive areas [ 48 , 49 ]. Patients with focal lesions of the dentate nuclei performed worse on cognitive testing than patients with cerebellar lesions sparing the dentate nuclei [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the dentate nuclei are strongly affected in SCA3. Cerebellar nuclei are the main output structures of the cerebellum, and similar to the cerebellar cortex there is compartmentalization of the dentate nuclei in motor and cognitive areas [ 48 , 49 ]. Patients with focal lesions of the dentate nuclei performed worse on cognitive testing than patients with cerebellar lesions sparing the dentate nuclei [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DCN send direct projections to the ventrolateral (VL) and the intralaminar thalamic nuclei, particularly the dorsomedial (MD) nucleus [ 125 ]. The VL nucleus, classically known as an integrative center for sensorimotor transformations, targets the primary motor cortex (M1) [ 42 , 126 , 127 ], whereas the MD nucleus, like other intralaminar nuclei, has widespread cortical projections including the mPFC ( Figure 3 A) and the superior temporal sulcus [ 128 , 129 , 130 , 131 , 132 ]. Past anatomical studies demonstrated that the cerebellum is interconnected with parts of the limbic system, including the hippocampus, amygdala, and cingulate cortex ( Figure 3 B) [ 133 , 134 ].…”
Section: Cerebellar Involvement In Asdmentioning
confidence: 99%
“…Second, as the FVN is under tumor compression, probabilistic tractography is somewhat superior to deterministic tractography for high curvature fiber tracts in the cerebellum. 62 Recent studies 61,63 have demonstrated the advantages of probabilistic tractography in crossing fibers in the cerebellum. Third, similar to the automatic identification pipeline in this study, a cerebellum tractography atlas can be created to automatically identify subject-specific fiber tracts in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…First, similar to small‐scale FVN, identifying highly extruded fiber tracts in the cerebellum requires high‐resolution dMRI data. Furthermore, multicompartment diffusion models based on multishell data 61 are recommended to ensure the accuracy of fiber orientation estimation. Second, as the FVN is under tumor compression, probabilistic tractography is somewhat superior to deterministic tractography for high curvature fiber tracts in the cerebellum 62 .…”
Section: Discussionmentioning
confidence: 99%